Effect of feeding regimen on meat quality, MyHC isoforms, AMPK, and PGC‐1α genes expression in the biceps femoris muscle of Mongolia sheep. Issue 5 (14th April 2020) - Hou, Yanru; Su, Lin; Su, Rina; Luo, Yulong; Wang, Bohui; Yao, Duo; Zhao, Lihua; Jin, Ye
Abstract: The effects of two feeding regimens on meat quality, myosin heavy chain (MyHC) types, and key factors regulating muscle fiber type (AMP‐activated protein kinase [AMPK] and peroxisome proliferator‐activated receptor‐coactivator‐1α [PGC‐1α]) in the biceps femoris muscle of Mongolia sheep were investigated. A total of 20 Mongolia sheep were weaning for 90 days and divided into two groups (pasture group (P) and confinement group (C)) at 10.36 ± 0.35 kg of weaning weight. After weaning, sheep were pasture fed or confinement fed for 9 months. The results showed that live weights, carcass weight, intramuscular fat (IMF), and Warner–Bratzler shear force (WBSF) in P group were significantly lower ( p  < .05) than that in C group. Compared with P group, color evaluations with respect to L* and b* values were significantly higher ( p  < .05) in C group. Expression of the MyHC I gene in the P group was significantly higher, while MyHC IIa and MyHC IIb genes expression was significantly lower ( p  < .05) than that in C group. Also, AMPK activity and expression of AMPKα2 and PGC‐1α genes were significantly higher ( p  < .05) in P group compared with C group. The present study indicated that muscle fiber composition was one of the key differences leading to the differences of meat quality in different feeding regimens. AMPK, particularly AMPKα2, and PGC‐1α were considered to be two key factors regulating muscle fiber types in Mongolia sheep. The results support that AMPK activity and the expression of AMPKα2 and PGC‐1α genes may affect the composition of muscle fibers; thus, AMPK activity and the expression of AMPKα2 and PGC‐1α genes had an effect on meat quality by changed composition of muscle fibers. Abstract : In present study, pasture sheep showed an advantage over confinement sheep with respect to WBSF of meat quality. And higher AMPK activity and expression of AMPKα2 and PGC‐1α genes caused by pasturing can promote the transformation of muscle fiber types from MyHC IIx, MyHC IIa, and MyHC IIb to MyHC I, which indicated that feeding regimen affect WBSF via alter muscle fiber types by regulating AMPK activity, and expression of AMPKα2 and PGC‐1α genes.